Um jogo de tabuleiro envolvendo conceitos de mineralogia no ensino de química - Santos, Karen Ouverney (Universidade Federal de São Carlos, 2021)
This paper describes the development and application of the board game "Minerals", aiming at teaching concepts of mineralogy in High School. Once concluded the artistic conception, assembly of pieces, boards and rules definition, the game was submitted to a team of undergraduate students in Chemistry, in order to assess its pedagogical potential, as well as its playfulness, dynamics and playability. Subsequently, the game was introduced to high school students from a state public school, in order to analyze its applicability and effectiveness in the teaching of concepts generally unexplored at this school level. Results showed an excellent acceptance of the game by the students, as well as its contribution to the learning of concepts on an important theme, which is very little explored in Basic Education. Furthermore, the work involved undergraduate students in Chemistry, whom had the opportunity of experiencing the development and application of a playful teaching tool.
A board game involving concepts of mineralogy in chemistry teaching
Keywords: Ensino de Química; Mineralogia; Jogo de tabuleiro; CIENCIAS EXATAS E DA TERRA::QUIMICA